A antropologia dos animais racionais dependentes - Carvalho, Helder Buenos Aires de (Pensando - Revista de Filosofia, 2011)
Resenha ampliada de: MacIntyre, Alasdair. Dependent Rational Animals: Why Human Beings Need the Virtues. Chicago, Illinois: Open Court Publishing Company, 1999. xiii, 172p. Hardback. (The Paul Carus Lectures Series, 20) ISBN 0-8126-9397-3.